Towards Service Level Agreement Quantification on Service-Based Computing - Irving Vitra Paputungan; Akmal Kurniadi Denna; Devi Rachmawati (Universitas Ahmad Dahlan, 2022)
A service Level Agreement is an agreement between service providers and consumers that contains the rights and obligations of both parties, particularly in terms of the delivery of services provided during the subscription period on service-based computing. Once approved, normally, the Service Level Agreement will not change until the end of the subscription period. SLA violations are often positioned between yes and no. As a result, service providers must deal with severe penalties or compensation. In this paper, the use of weightage for each SLA parameter is introduced in this paper. Such quantification using weightage is the main contribution. SLA violation detection cases in service-based computing are used to demonstrate how SLA quantification works. In the simulation scenario of SLA quantification, the presence of weightage and its aggregates along with the upper and lower bound is able to help the SLA violation detection process more appropriate. Violations are no longer seen between Yes and No, but the severity of the violation can also be determined. The number of violated parameters is not very influential in determining the level because the main determinant is the weightage. At the same time, the upper and lower limits are also very helpful in determining the level of violation. It is believed that SLA quantification is the way forward for better SLA management.